2003
DOI: 10.1080/16501970306094
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Adaptation of the Norwegian Versions of the Roland-Morris Disability Questionnaire and the Oswestry Disability Index

Abstract: The reliability and construct validity of the Norwegian versions of the Roland Morris Disability Questionnaire and the modified Oswestry Disability Index are acceptable for assessing functional status of Norwegian-speaking patients with low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
160
6
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(177 citation statements)
references
References 34 publications
10
160
6
1
Order By: Relevance
“…Although five individuals did ultimately return their second questionnaire, which they had completed from 17 to 25 days after the first, in the interests of homogeneity we chose not to include these data in the final analysis (though the data from these five patients was actually remarkably reliable: ICC for ODI 0.93; RM 0.91). The ICC reported in the present study for the German ODI was higher than those reported in previous studies, even though many of the latter used shorter test-retest intervals (median 4 days, ICC=0.91 [29]; 1 week, 0.83 [22], 0.94 [15]; 2 days, 0.88 [23], 2 weeks, 0.94 [26]; 4 weeks, 0.90 [21], 6 weeks, 0.84 [11]). The weighted j values for the individual questions were moderate to very good, ranging from 0.59 (for the ''lifting'' question) to 0.85 (for ''walking''); no j values for the ODI have previously been reported in the literature for comparison [32].…”
Section: Construct Validity Of the Odicontrasting
confidence: 80%
See 3 more Smart Citations
“…Although five individuals did ultimately return their second questionnaire, which they had completed from 17 to 25 days after the first, in the interests of homogeneity we chose not to include these data in the final analysis (though the data from these five patients was actually remarkably reliable: ICC for ODI 0.93; RM 0.91). The ICC reported in the present study for the German ODI was higher than those reported in previous studies, even though many of the latter used shorter test-retest intervals (median 4 days, ICC=0.91 [29]; 1 week, 0.83 [22], 0.94 [15]; 2 days, 0.88 [23], 2 weeks, 0.94 [26]; 4 weeks, 0.90 [21], 6 weeks, 0.84 [11]). The weighted j values for the individual questions were moderate to very good, ranging from 0.59 (for the ''lifting'' question) to 0.85 (for ''walking''); no j values for the ODI have previously been reported in the literature for comparison [32].…”
Section: Construct Validity Of the Odicontrasting
confidence: 80%
“…the degree of change required in a given individual's measures, in order to establish it (with a given level of confidence) as being a ''real change'', over and above measurement error. At the 95% confidence level, the MDC 95% for the ODI was 9 points-slightly lower than the values previously reported in the literature (13 points [21], 11 points [23], 10 points [25], 17 points [11]). An MDC 95% of 9 points indicates that, if an individual were to record a change of more than 9 points after a given intervention, then the odds would be 19 to 1 (i.e.…”
Section: Construct Validity Of the Odicontrasting
confidence: 66%
See 2 more Smart Citations
“…The self-perceived effectiveness of coping strategies to control pain (CSQ-COP) and ability to decrease pain (CSQ-ADP) were measured by two singleitem scales with a score range of 0-6 (low-high). In Scandinavian conditions, all questionnaires have been shown to have good reliability and validity [10,16,18,21,22,24,26,36].…”
Section: Evaluation Of Outcomementioning
confidence: 99%